A dynamic model for managing adulteration risks of dairy industry supply chain in Indonesia - Muhammad Arwani; Imam Santoso; Nuria Rahmatin (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2018)
Supply chain has a principal role in supporting the development of milk processing industry. The supply chain of the dairy industry in Indonesia involves a number of actors and a variety of dairy handling that may lead into potential risks and failures. One of the risks affecting supply chain performance is the adulteration of raw materials. This condition can possibly result in the occurrence of chain’s effect. Thus, it is necessary to build a dynamic model to handle such problems. Dynamic modeling was used in this study. For the initial phase, determination of supply chain risk factor was investigated. Second, modeling of supply chain mitigation risk was conducted by using dynamic system. Dynamic models were used to analyse complex problems with many variables involved. The problem analysis results were modeled in a dynamic system that has an aim to reduce the risk of adulteration. This research has successfully constructed a model consisted of one main variable that can potentially reduce the risk. The foremost recommended strategy was to improve the transparency of supply chain management.